Prevalence of psychiatric morbidity and cognitive impairment among non-communicable disease patients in Southern Chennai, Tamil Nadu - P Kavya; Divya Ilanchoorian; R Hari Krishnan (Journal of Family Medicine and Primary Care)
Introduction: According to the WHO, non-communicable diseases cause 71% of all deaths globally. Despite many studies showing a significant association between non-communicable diseases (NCDs) and cognitive decline, it is not researched in Tamil Nadu. Hence, this study was conducted to screen for psychiatric morbidity and cognitive impairment (CI) among NCD patients in Southern Chennai. Aims: The aim of this study was to estimate the prevalence of psychiatric morbidity and CI and their associated factors among NCD patients attending NCD clinics of tertiary care hospitals. Methods and Material: A cross-sectional study was carried out in NCD patients (n = 343) attending an NCD clinic in a tertiary care hospital. Basic sociodemographic and clinical details were obtained by a semi-structured questionnaire. Cognition function and psychiatric morbidity were assessed using mini-mental state examination, patient health questionnaire 9 and generalised anxiety disorder 7 tools, respectively. Results: The mean age of the study participants was 58 years. Of 343 participants, 19.2% had severe CI, 26.8% had severe depression, and 29.7% had severe anxiety. Among 180 participants aged 59–86 years, 25.5% participants had osteoarthritis; of these, 41.3% had severe CI (P < 0.0001), 82.6% had severe depression (P < 0.0001) and 63% had severe anxiety (P < 0.027), and their association was statistically significant. Conclusions: This study concludes that about one-fourth of the NCD patients suffered from CI and psychiatric morbidity, which are of rising concern. Musculoskeletal diseases are neglected to be assessed under NCDs, and in this study, osteoarthritis was found to be significantly associated with depression, anxiety and CI.